Analisis Tantangan Negara Hukum Dalam Menegakkan Hukum Tata Negara Di Era Digital - Savina Anggun Lestari; Muhammad Rijal Sadida; Risyan Putri Maharani; Intan Wahyuningtyas Andini (Jurnal Relasi Publik, 2023)
A rule of law is a country that upholds the rule of law as the main foundation in the administration of the state and government. In essence, a rule of law state also adheres to the meaning that every decision and action of the government must be based on law and mere will. It has been written clearly that the legal basis for the rule of law in Indonesia is contained in Article 1 Paragraph (3) of the 1945 Constitution which states that, "Indonesia is a country based on law". It is undeniable that in this Digital Age, Indonesia's challenges as a rule of law and its implementation are increasingly challenging. There are still many human rights violations, corruption and injustice in the justice system. To overcome these challenges, Indonesia has carried out many legal reforms. The purpose of this article is to find out how to analyze the challenges of the rule of law in enforcing constitutional law in the digital era. The type of research method used, using the method of literature study or literature review, by examining literature data that matches the theory within the scope of Constitutional Law. The results show that Indonesia as a rule of law country is still lacking in law enforcement and the justice system. In this digital era, technology has developed very rapidly, it also presents new challenges for constitutional law and of course also has an impact on the constitution. In conclusion, the existence of a rule of law remains important in this digital era in the implementation of constitutional law by adapting and developing an appropriate legal framework and strengthening the capacity of law enforcers to respond to these new emerging challenges.